Construcción de la hegemonía estadounidense : aislacionismo frente a Europa y hegemonía continental (2017)
ABSTRACT: In analysing the history of the United States, it is possible to observe a tendency to establish hegemonies consistent in the use of persuasion or economic and cultural influence rather than in the physical strength, circumstance with a direct impact on its relations with Hispanoamérica and the rest of the world. To define the hegemony will be mentioned some authors such as Antonio Gramsci, Alfonso Klauer, Carlos Pérez Morales, Immanuel Wallerstein, etc. In an attempt to explain the way in which American political and economic theories of the nineteenth and early twentieth centuries were articulated. It could be said that given the amplitude of the theme, emphasis will be placed on what happened between the signing of the Treaty of Versailles and the beginning of World War II. In addition, due to the few efforts that link US foreign policy relating to its actions in Europe and Latin America, both issues will be treated independently but following as a thread the thesis that the United States lived only a relative isolationism very reduced to its relations with Europe. Finally, emphasis will be placed on the possibilities of Latin America to take advantage of the multilateralism posed by modern international institutions, with which it can defend itself against abuses, demand for participation and create political paths of its own.